Characterization of street food consumption according to age, multicentric study - Duran Aguero, S (2018)
Introduction: The consumption of street food has become widespread in many countries, however, the reasons for consumption and perceptions by consumers about the hygiene of such food are unknown. Objective: To describe the consumption, the reasons for consumption and the perceptions of consumers about street food according to age group. Material and Methods: A survey of 15 questions was developed in Google Docs, adapted to each country, translated into Spanish or Portuguese and applied to 8895 people in 11 countries of Latin America (Argentina, Brazil, Chile, Colombia, Costa Rica, Guatemala, Panama, Paraguay, Peru, Portugal and Uruguay). Results: 53.6% of respondents indicate that they consume street food, the highest consumption (63.6%) occurs in the group of younger age (18-30 years), and decreases as age increases. The perception linked to dirtiness of food increases as age increases. On the other hand, as age increases, foods are preferred because they are tasty and they are available, in contrast to younger ones, where food is preferred due to economic factors and lack of time. Conclusions: As age increases, the consumption of street food decreases, the perception of good hygiene of these foods changes and the reasons for consumption are modified.